Pulmonary infiltration after exposure to home renovation dust: histopathology and microanalysis. - Anderson, K (1996)
A subacute self-resolving illness associated with bilateral pulmonary infiltration developed in a patient following renovation in her home. This may have been related to exposure to silicaceous plaster dust which was found in an environmental sample as well as on microanalysis of a transbronchial lung biopsy specimen and bronchoalveolar lavage fluid.